Production and processing technology of high-strength ceramic matrix composite bolt

Through thermal imaging analysis and clustering technology, the cracking characteristics and temperature adjustment factors of ceramic matrix composite bolts are evaluated, which solves the problem of difficulty in accurately analyzing the heat distribution inside the prefabricated body in the prior art, and realizes the optimization of bolt performance and scientific adjustment of cracking temperature.

CN119775017AActive Publication Date: 2025-04-08NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202510266607.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-08
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to accurately analyze the heat distribution uniformity and thermal response stability characteristics inside the prefabricated body of ceramic matrix composite bolts, resulting in a lack of scientific data support for cracking temperature adjustment, which may cause damage to the bolt performance.

Method used

By obtaining the thermal imaging map of the bolts of ceramic matrix composite materials during high-temperature cracking, analyzing the heat distribution differences and temperature gradient characteristics of each cell, a cracking characteristic factor is obtained, and a temperature adjustment factor is obtained through clustering technology to evaluate the sufficient degree of cracking of the bolt and adjust the cracking temperature.

Benefits of technology

The accurate analysis of the heat distribution inside the prefabricated body during the cracking process of ceramic matrix composite bolts is achieved, and scientific data support is provided, ensuring the optimization of the bolt performance and avoiding performance damage caused by improper cracking temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775017A_ABST
    Figure CN119775017A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ceramic matrix composite bolt preparation, in particular to a high-strength ceramic matrix composite bolt production and processing technology which comprises the following steps: obtaining a rod-shaped preform with a cladding structure and a core structure, hanging the rod-shaped preform in a vapor deposition furnace, and depositing a pyrolytic carbon interface layer on the fiber surface of the rod-shaped preform to obtain the high-strength ceramic matrix composite bolt. Carrying out high-temperature treatment; placing the treated rod-shaped prefabricated body in a vacuum dipping barrel; pumping the ceramic precursor slurry into a barrel, carrying out argon pressurization, heating, heat preservation and furnace cooling, then taking out the ceramic precursor slurry, respectively carrying out vacuum cracking treatment under low-temperature and high-temperature conditions, and after heat preservation, naturally cooling the ceramic precursor slurry to room temperature in an argon atmosphere; preparing a silicon carbide matrix to obtain segmented bars; the segmented bars are ground and machined; and a ceramic coating is prepared on the surface of the bolt with the outer threads machined, the ceramic coating is silicon carbide, and the ceramic-based composite material bolt is obtained. The method aims at optimizing the cracking temperature in the cracking treatment process of the ceramic matrix composite bolt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of preparation of ceramic matrix composite material bolts, and in particular to a production and processing technology for high-strength ceramic matrix composite material bolts. Background Art

[0002] Ceramic matrix composites are a type of composite material that uses ceramic as a matrix and various fibers as a composite material. They have excellent properties such as high temperature resistance, high strength and stiffness, relatively light weight, and corrosion resistance. As a type of connector, ceramic matrix composite bolts have broad application prospects in aerospace, automotive, energy, and military fields due to their excellent performance. They can not only improve the safety of related equipment, but also show excellent reliability in extreme environments. The research and application of ceramic matrix composite bolts are of great significance.

[0003] In the preparation process of ceramic-based composite bolts, a cracking treatment is required. This process can convert the ceramic precursor into a ceramic matrix with good mechanical properties and high-temperature stability, improve the stability of the material in a high-temperature environment, and optimize the mechanical and thermal properties of the material by controlling the crystal phase and microstructure of the material. However, the existing technology makes it difficult to accurately analyze the uniformity of heat distribution and the stability characteristics of thermal response inside the preform, and thus cannot provide scientific data support for the adjustment of the cracking temperature, which may cause the performance of the ceramic-based composite bolt to be impaired due to improper cracking temperature. Summary of the invention

[0004] In view of the above, it is necessary to provide a production and processing technology for high-strength ceramic-based composite bolts to solve the above problems.

[0005] An embodiment of the present application provides a production process for a high-strength ceramic matrix composite material bolt, the process comprising: S1: A rod-shaped preform having a cladding structure and a core structure is obtained by using silicon carbide fiber, and pre-treated; S2: The rod-shaped preform obtained in S1 is subjected to vacuum cracking treatment at low temperature and high temperature in turn, and after heat preservation, it is naturally cooled to room temperature in an argon atmosphere to obtain a densified rod; wherein, during the high temperature vacuum cracking process: S201: After a preset time of high temperature cracking, obtaining a thermal image of the ceramic matrix composite material bolt at each time; S202: obtaining a cracking characteristic factor of each pixel according to the difference in heat distribution between each pixel and pixels in a neighborhood range in the thermal imaging image of the ceramic matrix composite material bolt, and the temperature gradient distribution characteristics; S203: clustering pixels in the thermal image based on the cracking characteristic factors, and obtaining a temperature adjustment factor through the boundary distribution of each cluster in the thermal image and the stability of temperature change within a preset time period; S204: evaluating the degree of cracking sufficiency of the ceramic matrix composite material bolt by a temperature adjustment factor, and adjusting the cracking temperature; S3: The silicon carbide matrix is ​​prepared by chemical vapor infiltration, and the densified rod is cut into segmented rods of preset length according to the bolt length requirements; S4: Grinding the outer circle of the segmented bar stops when it meets the outer diameter conditions, and the processing is carried out according to the requirements of the bolt external thread; S5: A ceramic coating is prepared on the surface of the bolt after external thread processing by chemical vapor deposition, wherein the ceramic coating is silicon carbide, and a ceramic matrix composite material bolt is obtained.

[0006] The pre-processing process described in S1 is: S101: suspending the rod-shaped preform in a vapor deposition furnace, depositing a pyrolytic carbon interface layer on the fiber surface of the rod-shaped preform, and performing high temperature treatment; S102: placing the processed rod-shaped preform in a vacuum impregnation barrel; then, pumping the ceramic precursor slurry into the barrel, and taking it out after being pressurized by argon gas, heated, kept warm, and cooled with the furnace; S103: drain the slurry on the rod-shaped preform after the immersion, keep it warm, and then cool it down and take it out.

[0007] The core structure is a cylinder formed by multiple fiber bundles arranged in the same direction, wherein silicon carbide fibers account for 40% to 50% of the volume fraction of the entire cylinder.

[0008] The cladding structure is a tubular fiber bundle braided layer wrapped around the outer peripheral surface of the core structure, wherein the volume fraction of silicon carbide fibers in the tubular fiber bundle braided layer is 40% to 50%.

[0009] Wherein, the thickness of the pyrolytic carbon interface layer is: The high temperature treatment conditions are: 1700~1900℃, keeping warm for 1~1.5h.

[0010] Among them, the placing in the vacuum impregnation barrel includes vacuuming to -0.5~-0.05MPa and maintaining it for 60 minutes; the pressurizing, heating and heat preservation with argon gas are specifically pressurized to 0.8~1MPa, heated to 50°C and kept warm for 1~1.5 hours; wherein, the ceramic precursor slurry is obtained by placing polycarbosilane and xylene in a water bath at a mass ratio of 2:1, and mechanically stirring at 70°C and 60r / min for 3~5h to mix them evenly.

[0011] Wherein, obtaining the cracking characteristic factor of each pixel includes: A pixel window is established with each pixel as the center, and the temperature extreme difference value of the pixel window of each pixel in the thermal image at each moment is obtained; the temperature difference between each pixel and other pixels in its pixel window is calculated, and the neighborhood temperature difference of each pixel is obtained by combining the temperature extreme difference value; Obtain a negative correlation mapping result of the distance between each pixel and any pixel in its pixel window, fuse the negative correlation mapping result with the temperature difference between the corresponding two pixels, and obtain a temperature gradient between each pixel and any pixel in its pixel window; and use the average level of all the temperature gradients of each pixel as the temperature change index of each pixel; Based on the neighborhood temperature difference of each pixel and the temperature change index, the cracking characteristic factor of each pixel is obtained.

[0012] Wherein, obtaining the temperature adjustment factor includes: The absolute value of the difference of the cracking characteristic factors between pixels is used as the distance measurement method between pixels, and all pixels in the thermal image at each moment are clustered; the edge detection is performed on the thermal image at each moment; For each cluster in the thermal imaging image, the temperature difference between each cluster and the cluster center of all other clusters is fused to obtain the comprehensive temperature difference index of each cluster; the fusion result of the temperature difference between each boundary pixel in each cluster and all pixels in its neighborhood is obtained to obtain the boundary temperature difference value of each boundary pixel; the negative correlation mapping result after the boundary temperature difference value of all boundary pixels of each cluster is fused with the comprehensive temperature difference index is used as the thermal response factor of each cluster; The thermal response factors of all clusters in the thermal imaging image at each moment are arranged in order to form a thermal response feature vector of the thermal imaging image at each moment; the preset time period is used as a cracking temperature adjustment interval; For each cracking temperature adjustment interval, the temperature characteristic value of each moment is obtained according to the distance measurement between the thermal response characteristic vectors of each moment and the other moments, combined with the degree of confusion of the thermal response characteristic vectors of each moment; the sum of the temperature characteristic values ​​of all moments in each cracking temperature adjustment interval is normalized to obtain the temperature adjustment factor of each cracking temperature adjustment interval.

[0013] Wherein, the adjustment of the cracking temperature comprises: Set a sufficient cracking threshold. When the temperature adjustment factor obtained in real time is greater than or equal to the sufficient cracking threshold, no temperature adjustment is performed; otherwise, the temperature of the preset value is increased based on the current cracking temperature.

[0014] Wherein, the specific steps of preparing the silicon carbide substrate are: The ceramic matrix composite bolts after cracking treatment are placed in a chemical vapor infiltration furnace, with trichlorosilane as the precursor, hydrogen as the carrier gas and reducing gas, argon as the diluent gas, the deposition temperature is 800-900 ° C, the deposition time is 80-100 h, the deposition pressure is set to 15 kPa, the molar ratio of the reducing gas to trichlorosilane is 15:1, the precursor flow rate is 4 g / min, the dilution gas flow rate is 10 L / min, the flow rate of the reducing gas is determined by the molar ratio of the reducing gas to the silicon source, the carrier gas flow rate is 100 mL / min, until the final density of the material after the ceramic matrix is ​​prepared is: .

[0015] This application has at least the following beneficial effects: The present application obtains thermal imaging images during the cracking process of ceramic-based composite material bolts, analyzes the heat distribution status and temperature gradient characteristics within the neighborhood of the preform to obtain cracking characteristic factors, and adds consideration of the rapidity of temperature changes on the basis of analyzing the uniformity of heat distribution within the neighborhood of the preform, which more accurately reflects the ideal state of the cracking treatment effect at the pixel position; clusters the pixels in the thermal imaging image based on the cracking characteristic factors, and obtains the temperature adjustment factor through the boundary distribution of each cluster in the thermal imaging image and the stability of temperature changes within a preset time period, thereby evaluating the degree of cracking sufficiency of the ceramic-based composite material bolts, which is used as the data basis for cracking temperature adjustment, comprehensively considers the internal thermal response characteristics of the preform material during the cracking process and the consistency of the thermal response change trend, and more accurately quantifies the degree of cracking sufficiency of the ceramic-based composite material bolts, providing scientific data support for the optimization and adjustment of the cracking temperature during the cracking process of the ceramic-based composite material bolts, avoiding uneven heat inside the preform caused by improper cracking temperature, and insufficient cracking inside the preform affecting the performance of the prepared ceramic-based composite material bolts. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A flow chart of a production and processing process for a high-strength ceramic matrix composite bolt provided in this application; Figure 2 A flow chart of preprocessing the rod-shaped preform provided in the present application; Figure 3 A schematic diagram of changes in the porosity and density of the preform during the high-temperature cracking process provided in this application; Figure 4 A specific flow chart for adjusting the high-temperature cracking temperature provided in this application. DETAILED DESCRIPTION

[0017] In the description of the embodiments of the present application, words such as "exemplary", "or", "for example" and the like are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary", "or", "for example" and the like is intended to present related concepts in a concrete manner.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art in the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0019] It should also be noted that the terms "first" and "second" in this application and its drawings are used to distinguish similar objects, rather than to describe a specific order or sequence. The method disclosed in the embodiments of the present application or the method shown in the flow chart includes one or more steps for implementing the method. Without departing from the scope of protection of this application, the execution order of multiple steps can be interchanged with each other, and some steps can also be deleted.

[0020] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0021] The present application embodiment provides a production and processing technology for a high-strength ceramic matrix composite material bolt, which is applied to the field of ceramic matrix composite material bolt preparation. Figure 1 , the process comprises: S1: A rod-shaped preform having a cladding structure and a core structure is obtained by using silicon carbide fiber, and pre-treated.

[0022] (1) Determine the size of the fiber preform and design the fiber preform structure.

[0023] According to the required size requirements of the ceramic matrix composite bolt, the size of its fiber preform is designed. The fiber preform includes a core structure and a cladding structure. The core structure is a cylinder formed by multiple fiber bundles arranged in the same direction; the cladding structure is a tubular fiber bundle braided layer wrapped around the outer circumference of the core structure. Among them, the fiber is silicon carbide fiber, and the size of the prepared ceramic matrix composite bolt is: small diameter 6mm, large diameter 8mm. Silicon carbide fiber is used as the material of the fiber preform. The core structure diameter of the carbon fiber preform is designed to be 5.5mm, and the outer diameter of the cladding is 8.5mm.

[0024] (2) Prepare the core structure.

[0025] Prepare a fiber bundle with a length of 1500mm, and use a round rod with a length of 1485mm and a diameter of 5.5mm as a bundle mold; multiple fiber bundles are distributed on the surface of the round rod in a manner that each fiber bundle extends along the axial direction of the round rod, and multiple fiber bundles are closely arranged along the circumference of the round rod until the entire round rod is wrapped. Bundle one end of the fiber bundle that exceeds the end face of the round rod with a 1K silicon carbide fiber bundle, then remove the metal round rod, straighten all the fiber bundles, and bundle the other end with a 1K silicon carbide fiber bundle. Maintain the tension of the fiber bundle, bundle it with molten glass fibers in a spiral direction, form a core structure of unidirectional fiber bundles, and keep it straightened. Among them, in the core structure of this embodiment, silicon carbide fibers account for 40% of the volume fraction of the entire cylinder; in the core structure of other embodiments, silicon carbide fibers account for 43% of the volume fraction of the entire cylinder; in the core structure of some other embodiments, silicon carbide fibers account for 50% of the volume fraction of the entire cylinder.

[0026] (3) Prepare the cladding structure.

[0027] While the unidirectional fiber bundle core structure is kept straightened, a fiber bundle cladding is woven on its surface by a three-dimensional four-way weaving method, and the fiber bundle weaving tension is set, so that the unidirectional fiber bundle core structure preform is subjected to the compressive stress of the cladding weaving preform. Among them, in the cladding structure of this embodiment, the volume fraction of silicon carbide fibers in the tubular fiber bundle woven layer is 40%; in the cladding structure of other embodiments, the volume fraction of silicon carbide fibers in the tubular fiber bundle woven layer is 45%; in some other embodiments, the volume fraction of silicon carbide fibers in the tubular fiber bundle woven layer is 50%.

[0028] (4) Stitching the core and cladding structures to obtain a rod-shaped preform.

[0029] Using fine molten glass filaments, under the guidance of a metal needle, stitching is performed once along the 0° and 90° directions of the cross section of the preform obtained in (3), and then stitching is continued once along the 0° and 90° directions of the cross section after a set length along the axial interval. The above stitching steps are repeated to form a rod-shaped preform with a cladding of a tubular fiber bundle woven layer structure and a core of a cylindrical structure formed by multiple fiber bundles arranged in the same direction.

[0030] The rod-shaped preform is pretreated, and the pretreatment process includes: S101: The rod-shaped preform is suspended in a vapor deposition furnace, a pyrolytic carbon interface layer is deposited on the fiber surface of the rod-shaped preform, and a high-temperature treatment is performed.

[0031] The rod-shaped preform is suspended in a vapor deposition furnace, and a pyrolytic carbon interface layer is deposited on the fiber surface of the rod-shaped preform using a CVI deposition process. The thickness range of the pyrolytic carbon interface layer is: ; The rod-shaped preform with deposited pyrolytic carbon interface layer is subjected to high temperature treatment. In this embodiment, the high temperature treatment conditions are: 1700°C, and keep warm for 1.5 hours; in other embodiments, the high temperature treatment conditions are: 1750°C, and keep warm for 1.5 hours; in some other embodiments, the high temperature treatment conditions are: 1900°C, and keep warm for 1 hour.

[0032] S102: placing the processed rod-shaped preform in a vacuum impregnation barrel; then, pumping the ceramic precursor slurry into the barrel, and taking it out after being pressurized by argon gas, heated, kept warm, and cooled with the furnace.

[0033] The rod-shaped preform treated with S101 is placed in a vacuum impregnation barrel. In this embodiment, the vacuum is evacuated to -0.5 MPa and maintained for 60 minutes; in other embodiments, the vacuum is evacuated to -0.05 MPa; in some other embodiments, the vacuum is evacuated to -0.4 MPa.

[0034] Thereafter, the ceramic precursor slurry is pumped into a vacuum impregnation barrel so that the rod-shaped preform is completely submerged in the precursor slurry, and protective argon gas is introduced. In this embodiment, the pressure is increased to 0.8 MPa, the temperature is slowly increased to 50°C, and the temperature is kept for 1 hour, and the temperature is cooled down to room temperature with the furnace before being taken out; in other embodiments, the pressure is increased to 1 MPa, the temperature is slowly increased to 50°C, and the temperature is kept for 1.5 hours, and the temperature is cooled down to room temperature with the furnace before being taken out; in some other embodiments, the pressure is increased to 1 MPa, the temperature is slowly increased to 50°C, and the temperature is kept for 1 hour, and the temperature is cooled down to room temperature with the furnace before being taken out.

[0035] The ceramic precursor slurry is obtained by placing polycarbosilane and xylene in a water bath at a mass ratio of 2:1, and mechanically stirring at a speed of 60 r / min at 70°C. In this embodiment, the slurry is obtained after stirring for 3 hours to mix evenly; in other embodiments, the slurry is stirred for 3.5 hours; in some other embodiments, the stirring time is 5 hours.

[0036] S103: drain the slurry on the rod-shaped preform after the immersion, keep it warm, and then cool it down and take it out.

[0037] The slurry on the rod-shaped preform after impregnation is drained and placed in a preheated oven. In this embodiment, the preform is kept at 120°C for 7 hours at a heating rate of 10°C / min; in other embodiments, the preform is kept at 120°C for 5 hours at a heating rate of 10°C / min; in other embodiments, the preform is kept at 180°C for 4 hours at a heating rate of 10°C / min; and then naturally cooled to room temperature in the furnace and taken out.

[0038] Among them, the flowchart of the rod-shaped preform pretreatment is as follows Figure 2 shown.

[0039] S2: The rod-shaped preform obtained in S1 is subjected to vacuum cracking treatment under low temperature and high temperature conditions in turn, and after heat preservation, it is naturally cooled to room temperature in an argon atmosphere to obtain a densified rod.

[0040] Low-temperature pyrolysis: The rod-shaped preform after the above-mentioned solidification treatment is placed in a sintering furnace. In this embodiment, the temperature is evacuated to 60Pa, and the temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept for 3 hours. After naturally cooling to room temperature under an argon atmosphere, it is taken out; in some other embodiments, the temperature is evacuated to 90Pa, and the temperature is increased to 1000°C at a heating rate of 10°C / min, and the temperature is kept for 3 hours; in some other embodiments, the temperature is evacuated to 100Pa, and the temperature is increased to 1000°C at a heating rate of 10°C / min, and the temperature is kept for 2 hours.

[0041] High-temperature pyrolysis: The rod-shaped preform after low-temperature pyrolysis is placed in a sintering furnace. In this embodiment, the temperature is evacuated to 60Pa, and the temperature is increased to 1100°C at a heating rate of 10°C / min, and the temperature is kept for 3 hours. After naturally cooling to room temperature under an argon atmosphere, it is taken out; in some other embodiments, the temperature is evacuated to 80Pa, and the temperature is increased to 1100°C at a heating rate of 10°C / min, and the temperature is kept for 3 hours; in some other embodiments, the temperature is evacuated to 100Pa, and the temperature is increased to 1300°C at a heating rate of 10°C / min, and the temperature is kept for 2 hours.

[0042] Among them, during the high temperature vacuum cracking process: S201: After the high temperature cracking is performed for a preset time, a thermal image of the ceramic matrix composite material bolt is obtained at each time.

[0043] In order to analyze the cracking treatment effect of ceramic-based composite material bolts during the cracking process, as a scientific basis for cracking temperature control, this application collects relevant data during the cracking process of ceramic-based composite material bolts through a SCADA (Supervisory Control And Data Acquisition) system. The specific collection method is: after the rod-shaped preform after low-temperature cracking is placed in a sintering furnace and subjected to high-temperature cracking treatment for 30 minutes, an infrared thermal imager is used to obtain a thermal image of the ceramic-based composite material bolt. The time interval for obtaining the thermal image is 5s; the implementer can adjust it according to the actual situation; in order to prevent the noise interference in the thermal image of the obtained ceramic-based composite material bolt from seriously affecting the subsequent analysis, the histogram equalization method is used to perform image enhancement processing on the collected thermal image. Since the histogram equalization method is a well-known technology, the specific acquisition process will not be described in detail.

[0044] The thermal imaging image of the ceramic matrix composite material bolt is referred to as a thermal imaging image for the convenience of subsequent description. The thermal imaging image obtained by the above method is transmitted to the data statistical analysis module of the SCADA system.

[0045] S202: Obtain a cracking characteristic factor for each pixel according to the difference in heat distribution between each pixel and pixels in a neighborhood range in the thermal imaging image of the ceramic matrix composite material bolt, as well as temperature gradient distribution characteristics.

[0046] Under ideal conditions during the cracking process of ceramic-based composite bolts, as the temperature slowly rises, the heat distribution at each position of the ceramic-based composite bolt is uniform; when the temperature difference between the corresponding position and the adjacent position of the thermal imaging image of the ceramic-based composite bolt during the cracking process is more significant, it means that the cracking treatment effect of the preform is worse, and it is easier to reduce the performance of the ceramic-based composite bolts prepared subsequently.

[0047] Based on the above analysis, a pixel window is established with each pixel as the center to obtain the temperature extreme difference value in the pixel window of each pixel in the thermal imaging image at each moment; the temperature difference between each pixel and other pixels in its pixel window is calculated, and the neighborhood temperature difference of each pixel is obtained by combining the temperature extreme difference value.

[0048] In this embodiment, a thermal image at any time is taken as an example for subsequent analysis, and a pixel window is constructed with each pixel in the thermal image as the center. The pixel window size is ; Implementers can make adjustments based on actual conditions, and this application does not impose any restrictions on this.

[0049] The neighborhood temperature difference of the i-th pixel can be calculated as follows: ;in, is the neighborhood temperature difference of the i-th pixel in the thermal image; is the temperature extreme difference value in the pixel window corresponding to the i-th pixel in the thermal image; It is the cumulative result of the absolute value of the temperature difference between the i-th pixel in the thermal image and all the pixels in its pixel window.

[0050] It should be understood that when the cracking treatment effect of the ceramic-based composite material bolt is more ideal, the heat distribution inside the preform is more uniform, and the temperature difference within the neighborhood is smaller, that is, the difference between the maximum temperature value and the minimum temperature value in the pixel window is smaller, and the temperature value difference between all pixels in the pixel window and the central pixel is smaller.

[0051] Under normal circumstances, during the cracking process of ceramic-based composite bolts, the more significant the rapid change in the temperature gradient inside the preform, the less ideal the cracking treatment effect of the preform, and the more likely the discontinuity of heat transfer will affect the performance of the prepared ceramic-based composite bolts.

[0052] Based on the above analysis, the negative correlation mapping result of the distance between each pixel and any pixel in its pixel window is obtained, and the result is fused with the temperature difference between the corresponding two pixels to obtain the temperature gradient between each pixel and any pixel in its pixel window; the average level of all the temperature gradients of each pixel is taken as the temperature change index of each pixel.

[0053] In this embodiment, the distance between pixels is measured by Euclidean distance, and the negative correlation mapping result of the variable is specifically the inverse of the variable; multiple variables are fused by multiplication, that is, the temperature gradient is specifically the absolute value of the temperature difference between each pixel and any pixel in its pixel window divided by the distance between the corresponding two pixels. Specifically, the sharpness of the temperature change of the i-th pixel can be calculated as follows: ;in, is the temperature change index of the i-th pixel in the thermal image; is the total number of pixels in the pixel window; is the absolute value of the temperature difference between the i-th pixel in the thermal image and the j-th pixel in its pixel window; is the Euclidean distance between the i-th pixel in the thermal image and the j-th pixel in its pixel window; Represents the temperature gradient between the i-th pixel in the thermal image and the j-th pixel in its pixel window.

[0054] It should be understood that during the cracking process of ceramic-based composite bolts, the better the heat transfer effect inside the preform, the smaller the temperature gradient within the neighborhood of the preform, and the more blurred the phenomenon of rapid temperature change, that is, the smaller the cumulative ratio of the temperature difference to the distance difference between all pixels in the pixel window and the central pixel.

[0055] Generally speaking, when the heat distribution of the ceramic matrix composite bolt is more uniform during the cracking process and the temperature change phenomenon is more blurred, it can better reflect the characteristics of sufficient cracking treatment inside the preform. Based on the neighborhood temperature difference of each pixel and the temperature change index, the cracking characteristic factor of each pixel is obtained.

[0056] In this embodiment, the product of the neighborhood temperature difference of each pixel and the temperature change index is calculated, and the inverse of the product is used as the cracking characteristic factor of each pixel; it should be noted that in order to avoid the situation where the denominator is zero, it is necessary to add a preset value to the denominator, and the preset value in the embodiment is 0.1.

[0057] It should be understood that when the cracking treatment effect of the ceramic-based composite material bolt is more ideal, the heat distribution within the neighborhood of the preform is more uniform, the temperature gradient is smaller, the heat transfer is smoother, and the cracking characteristic factor is larger, that is, the neighborhood temperature difference is smaller and the temperature change degree is smaller.

[0058] S203: Clustering the pixels in the thermal image based on the cracking characteristic factors, and obtaining the temperature adjustment factor through the boundary distribution of each cluster in the thermal image and the stability of the temperature change within a preset time period.

[0059] All pixels in the thermal image at any moment are used as input, and the K-mediods clustering algorithm is used to obtain the various clusters and cluster centers in the thermal image, wherein the number of cluster centers is set to 10, and the absolute value of the difference in the cracking characteristic factors between pixels is used as the distance measurement method between pixels. Since the K-mediods clustering algorithm is a well-known technology, the specific acquisition process will not be described in detail. The purpose of using the K-mediods clustering algorithm in this application is to obtain the most representative cluster center in the clusters with similar cracking characteristics in the thermal image at any moment through the clustering algorithm, so as to facilitate the subsequent further analysis of the cracking characteristics of the ceramic matrix composite material bolts in the cluster, and then provide accurate data support for the cracking temperature control.

[0060] During the cracking process of the ceramic matrix composite bolt, the porosity inside the preform will gradually decrease, thereby improving the density inside the preform. The more fully the ceramic matrix composite bolt is cracked, the more obvious the thermal response characteristics inside the preform are, that is, the temperature difference between different areas is smaller, and because the temperature distribution is more uniform, the thermal boundary phenomenon between different areas inside the preform is smaller.

[0061] Among them, the schematic diagram of the changes in the porosity and density of the preform during high-temperature pyrolysis is shown in Figure 2. Figure 3 As shown, the horizontal axis is time, the unit is min, the left vertical axis is porosity, and the right vertical axis is density, all in %; wherein, as the preform pyrolysis treatment proceeds, the pores inside the preform gradually decrease and the density increases. When the pyrolysis temperature is inappropriate, the pore closure of the ceramic-based composite material inside the preform may be hindered, causing porosity rebound. At this time, the pyrolysis temperature of the ceramic-based composite material bolt should be adjusted in time to avoid affecting the pyrolysis treatment effect of the preform.

[0062] Based on the above analysis, we now take any moment as an example for subsequent analysis, and screen the boundary pixels in each cluster of the thermal image. The screening method is as follows: take the thermal image as input, use the edge detection algorithm based on the Canny operator to obtain all the edges in the thermal image, record the edge farthest from the cluster center in each cluster as the thermal boundary of each cluster, and record all pixels on the thermal boundary as the boundary pixels of the corresponding cluster. Among them, Canny edge detection is an existing well-known technology, which will not be repeated in this application. The implementer can choose other edge detection algorithms, and this application does not limit this.

[0063] For each cluster in the thermal imaging image, the temperature difference between each cluster and the cluster center of all other clusters is fused to obtain the comprehensive temperature difference index of each cluster; the fusion result of the temperature difference between each boundary pixel in each cluster and all pixels in its neighborhood is obtained to obtain the boundary temperature difference value of each boundary pixel; the negative correlation mapping result after the boundary temperature difference value of all boundary pixels of each cluster is fused with the comprehensive temperature difference index is used as the thermal response factor of each cluster.

[0064] In this embodiment, the comprehensive temperature difference index is specifically the cumulative sum of the absolute values ​​of the temperature differences between each cluster and the cluster centers of all other clusters; the boundary temperature difference value of each boundary pixel is specifically the cumulative sum of the absolute values ​​of the temperature differences between each boundary pixel in each cluster and all pixels in its neighborhood; the thermal response factor is specifically: calculating the sum of the boundary temperature difference values ​​of all boundary pixels in each cluster, and taking the inverse of the sum multiplied by the comprehensive temperature difference index as the thermal response factor of each cluster.

[0065] It should be understood that when the cracking treatment of the ceramic-based composite material bolts is more thorough, the thermal response characteristics inside the preform are more obvious, the temperature difference between different regions is slighter, the thermal boundary phenomenon is slighter, and the thermal response factor is larger, that is, the temperature difference between the corresponding cluster centers of different clusters is smaller, and the temperature difference between all boundary pixels in the cluster and all pixels in its neighborhood is slighter.

[0066] Generally speaking, when the ceramic-based composite material bolt is cracked more completely, the thermal response condition inside the preform becomes more stable over time, that is, the thermal response characteristic change trend inside the preform becomes more consistent over time.

[0067] Based on the above analysis, the sequence of thermal response factors of all clusters in the thermal imaging image at any moment in ascending order is used as the thermal response feature vector of the thermal imaging image at the corresponding moment, and every 30 minutes is used as a cracking temperature adjustment interval. The implementer can adjust the length of the cracking temperature adjustment interval according to the actual situation. Now take any cracking temperature adjustment interval as an example for subsequent analysis.

[0068] For each cracking temperature adjustment interval, the temperature characteristic value of each moment is obtained according to the distance measurement between the thermal response characteristic vectors of each moment and the other moments, combined with the degree of confusion of the thermal response characteristic vectors of each moment; the sum of the temperature characteristic values ​​of all moments in each cracking temperature adjustment interval is normalized to obtain the temperature adjustment factor of each cracking temperature adjustment interval.

[0069] Specifically, the temperature adjustment factor for the qth cracking temperature adjustment interval can be calculated as follows: ;in, is the temperature adjustment factor of the qth cracking temperature adjustment interval; is the total number of moments in the cracking temperature adjustment interval; is the cumulative result of the DTW distance between the thermal response feature vectors corresponding to the hth moment and all other moments in the qth cracking temperature adjustment interval; is the information entropy of the thermal response feature vector corresponding to the hth moment in the qth cracking temperature adjustment interval; norm[] is the normalization function, so that The value range is between [0,1].

[0070] It should be understood that when the cracking treatment of the ceramic-based composite material bolt is more thorough, the trend of change of the thermal response characteristics inside the preform will be more consistent over time, the difference between the thermal response characteristic vectors at different times within the cracking temperature adjustment interval will be smaller, and the difference in thermal response characteristics between different clusters in the thermal imaging image corresponding to each moment within the cracking temperature adjustment interval will be smaller, that is, the cumulative result of the DTW distance between the thermal response characteristic vectors corresponding to all moments in the cracking temperature adjustment interval and the remaining moments will be smaller, and the information entropy of the thermal response characteristic vectors corresponding to all moments in the cracking temperature adjustment interval will be smaller. At this time, there is no need to adjust the cracking temperature of the ceramic-based composite material bolt to avoid uneven heat inside the preform due to improper cracking temperature, and insufficient cracking inside the preform will affect the performance of the ceramic-based composite material bolt prepared subsequently.

[0071] S204: Evaluate the degree of cracking of the ceramic matrix composite material bolt by using a temperature adjustment factor, and adjust the cracking temperature.

[0072] Set the cracking sufficient threshold V, and obtain the temperature adjustment factor of any cracking temperature adjustment interval according to the above steps through the data acquisition and analysis module in the SCADA system. Transmit the real-time obtained temperature adjustment factor to the early warning management module in the SCADA system to conduct real-time evaluation of the cracking sufficient degree of the ceramic matrix composite material bolt. The specific evaluation method is as follows: When the temperature adjustment factor obtained in real time is greater than or equal to the sufficient cracking threshold value V, it is determined that the heat distribution inside the preform in the cracking temperature adjustment interval is uniform, the thermal response characteristics are stable, and there is no need to adjust the cracking temperature of the ceramic-based composite material bolt; when the temperature adjustment factor obtained in real time is less than the sufficient cracking threshold value V, it is determined that the heat distribution inside the preform in the cracking temperature adjustment interval is uneven, the heat transfer is not smooth, and the thermal response stability characteristics at various positions inside the preform are not obvious. It is necessary to increase the temperature by R℃ based on the current cracking temperature to further promote the sufficient cracking of the ceramic-based composite material bolt; The value range of the sufficient cracking threshold V is between [0,1]. The larger V is, the higher the cracking requirement for the ceramic-based composite material bolts. In this application, the sufficient cracking threshold V and the preset value R are taken as 0.6 and 30 respectively. The implementer can set the sufficient cracking threshold V and the preset value R according to the actual situation.

[0073] Among them, the specific flow chart for adjusting the high temperature cracking temperature is as follows: Figure 4 shown.

[0074] S3: The silicon carbide matrix is ​​prepared by chemical vapor infiltration, and the densified rod is cut into segmented rods of preset length according to the bolt length requirements.

[0075] The silicon carbide matrix is ​​prepared by chemical vapor infiltration, and the internal pores of the rod-shaped preform after the above-mentioned cracking treatment are sealed to further densify the ceramic matrix. The specific treatment method is: the ceramic-based composite material bolt after the cracking treatment is placed in a chemical vapor infiltration furnace, trichlorosilane is used as a precursor, hydrogen is used as a carrier gas and a reducing gas, and argon is used as a dilution gas. In this embodiment, the deposition temperature is 800°C and the deposition time is 100h; in some other embodiments, the deposition temperature is 800°C and the deposition time is 80h; in some other embodiments, the deposition temperature is 900°C and the deposition time is 80h; the deposition pressure is set to 15kPa, the molar ratio of the reducing gas to trichlorosilane is 15:1, the precursor flow rate is 4g / min, the dilution gas flow rate is 10L / min, the flow rate of the reducing gas is determined by the molar ratio of the reducing gas to the silicon source, and the carrier gas flow rate is 100mL / min, until the final density of the material after the ceramic matrix is ​​prepared is: 2.4~2.8 , the matrix densification treatment is completed to obtain a densified rod.

[0076] According to the bolt length requirements, the densified rods are cut into segmented rods with a length of 80 mm using a diamond tool.

[0077] S4: Grinding of the segmented bar stops when the outer diameter meets the outer diameter conditions, and the grinding is carried out according to the requirements of the bolt external thread.

[0078] The outer diameter of the segmented bar is ground with a centerless grinder until the outer diameter of the bar is equal to the major diameter of the bolt. The segmented bar with qualified outer diameter is processed to the qualified size according to the requirements of the bolt external thread using a diamond tool.

[0079] S5: Using chemical vapor deposition, a ceramic coating is prepared on the surface of the bolt after the external thread is processed. The ceramic coating is silicon carbide, and a ceramic matrix composite material bolt is obtained. In this embodiment, the coating thickness is 100 .

[0080] The flowchart and block diagram in the accompanying drawings show the possible architecture, function and operation of the system, method and computer program product according to the embodiment of the present application. In this regard, each box in the flowchart or block diagram can represent a module, a program segment or a part of the code, and the module, the program segment or a part of the code contains one or more executable instructions for realizing the specified logical function. In some alternative implementations, the function marked in the box can also occur in a different order from the order marked in the accompanying drawings. For example, two continuous boxes can actually be executed substantially in parallel, and they can sometimes be executed in the opposite order, which can depend on the functions involved. In the description corresponding to the flowchart and the block diagram in the accompanying drawings, the operations or steps corresponding to different boxes can also occur in a different order from the order disclosed in the description, and sometimes there is no specific order between different operations or steps. For example, two continuous operations or steps can actually be executed substantially in parallel, and they can sometimes be executed in the opposite order, which can depend on the functions involved. Each block in the block diagrams and / or flowcharts, and combinations of blocks in the block diagrams and / or flowcharts, may be implemented by a dedicated hardware-based system that performs the specified functions or actions, or may be implemented by a combination of dedicated hardware and computer instructions.

[0081] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A production and processing technology for high-strength ceramic-based composite bolts, characterized in that: The process includes: S1: A rod-shaped preform having a cladding structure and a core structure is obtained by using silicon carbide fiber, and pre-treated; S2: The rod-shaped preform obtained in S1 is subjected to vacuum cracking treatment at low temperature and high temperature in turn, and after heat preservation, it is naturally cooled to room temperature in an argon atmosphere to obtain a densified rod; wherein, during the high temperature vacuum cracking process: S201: After a preset time of high temperature cracking, obtaining a thermal image of the ceramic matrix composite material bolt at each time; S202: obtaining a cracking characteristic factor of each pixel according to the difference in heat distribution between each pixel and pixels in a neighborhood range in the thermal imaging image of the ceramic matrix composite material bolt, and the temperature gradient distribution characteristics; S203: clustering pixels in the thermal image based on the cracking characteristic factors, and obtaining a temperature adjustment factor through the boundary distribution of each cluster in the thermal image and the stability of temperature change within a preset time period; S204: evaluating the degree of cracking sufficiency of the ceramic matrix composite material bolt by a temperature adjustment factor, and adjusting the cracking temperature; S3: The silicon carbide matrix is ​​prepared by chemical vapor infiltration, and the densified rod is cut into segmented rods of preset length according to the bolt length requirements; S4: Grinding the outer circle of the segmented bar stops when it meets the outer diameter conditions, and the processing is carried out according to the requirements of the bolt external thread; S5: A ceramic coating is prepared on the surface of the bolt after external thread processing by chemical vapor deposition, wherein the ceramic coating is silicon carbide, and a ceramic matrix composite material bolt is obtained.

2. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 1, characterized in that: The pre-processing process described in S1 is: S101: suspending the rod-shaped preform in a vapor deposition furnace, depositing a pyrolytic carbon interface layer on the fiber surface of the rod-shaped preform, and performing high temperature treatment; S102: placing the processed rod-shaped preform in a vacuum impregnation barrel; then, pumping the ceramic precursor slurry into the barrel, and taking it out after being pressurized by argon gas, heated, kept warm, and cooled with the furnace; S103: drain the slurry on the rod-shaped preform after the immersion, keep it warm, and then cool it down and take it out.

3. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 1, characterized in that: The core structure is a cylinder formed by multiple fiber bundles arranged in the same direction, wherein silicon carbide fibers account for 40% to 50% of the volume fraction of the entire cylinder.

4. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 1, characterized in that: The cladding structure is a tubular fiber bundle braided layer wrapped around the outer peripheral surface of the core structure, wherein the volume fraction of silicon carbide fibers in the tubular fiber bundle braided layer is 40% to 50%.

5. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 2, characterized in that: The thickness of the pyrolytic carbon interface layer is: The high temperature treatment conditions are: 1700~1900℃, keeping warm for 1~1.5h.

6. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 2, characterized in that: The method of placing the ceramic precursor slurry in a vacuum impregnation barrel includes evacuating to -0.5~-0.05MPa and maintaining it for 60 minutes; the method of pressurizing, heating and keeping warm with argon gas includes pressurizing to 0.8~1MPa, heating to 50°C and keeping warm for 1~1.5 hours; wherein, the method of obtaining the ceramic precursor slurry is: polycarbosilane and xylene are placed in a water bath at a mass ratio of 2:1, and mechanically stirred at a speed of 60r / min for 3~5h at 70°C to mix them evenly.

7. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 1, characterized in that: The method of obtaining the cracking characteristic factor of each pixel includes: A pixel window is established with each pixel as the center, and the temperature extreme difference value of the pixel window of each pixel in the thermal image at each moment is obtained; the temperature difference between each pixel and other pixels in its pixel window is calculated, and the neighborhood temperature difference of each pixel is obtained by combining the temperature extreme difference value; Obtain a negative correlation mapping result of the distance between each pixel and any pixel in its pixel window, fuse the negative correlation mapping result with the temperature difference between the corresponding two pixels, and obtain a temperature gradient between each pixel and any pixel in its pixel window; and use the average level of all the temperature gradients of each pixel as the temperature change index of each pixel; Based on the neighborhood temperature difference of each pixel and the temperature change index, the cracking characteristic factor of each pixel is obtained.

8. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 1, characterized in that: The step of obtaining the temperature adjustment factor comprises: The absolute value of the difference of the cracking characteristic factors between pixels is used as the distance measurement method between pixels, and all pixels in the thermal image at each moment are clustered; the edge detection is performed on the thermal image at each moment; For each cluster in the thermal imaging image, the temperature difference between each cluster and the cluster center of all other clusters is fused to obtain the comprehensive temperature difference index of each cluster; the fusion result of the temperature difference between each boundary pixel in each cluster and all pixels in its neighborhood is obtained to obtain the boundary temperature difference value of each boundary pixel; the negative correlation mapping result after the boundary temperature difference value of all boundary pixels of each cluster is fused with the comprehensive temperature difference index is used as the thermal response factor of each cluster; The thermal response factors of all clusters in the thermal imaging image at each moment are arranged in order to form a thermal response feature vector of the thermal imaging image at each moment; the preset time period is used as a cracking temperature adjustment interval; For each cracking temperature adjustment interval, the temperature characteristic value of each moment is obtained according to the distance measurement between the thermal response characteristic vectors of each moment and the other moments, combined with the degree of confusion of the thermal response characteristic vectors of each moment; the sum of the temperature characteristic values ​​of all moments in each cracking temperature adjustment interval is normalized to obtain the temperature adjustment factor of each cracking temperature adjustment interval.

9. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 1, characterized in that: The step of adjusting the cracking temperature comprises: Set a sufficient cracking threshold. When the temperature adjustment factor obtained in real time is greater than or equal to the sufficient cracking threshold, no temperature adjustment is performed; otherwise, the temperature of the preset value is increased based on the current cracking temperature.

10. The production and processing technology of a high-strength ceramic matrix composite material bolt according to claim 1, characterized in that: The specific steps of preparing the silicon carbide substrate are: The ceramic matrix composite bolts after cracking treatment are placed in a chemical vapor infiltration furnace, with trichlorosilane as the precursor, hydrogen as the carrier gas and reducing gas, argon as the diluent gas, the deposition temperature is 800-900 ° C, the deposition time is 80-100 h, the deposition pressure is set to 15 kPa, the molar ratio of the reducing gas to trichlorosilane is 15:1, the precursor flow rate is 4 g / min, the dilution gas flow rate is 10 L / min, the flow rate of the reducing gas is determined by the molar ratio of the reducing gas to the silicon source, the carrier gas flow rate is 100 mL / min, until the final density of the material after the ceramic matrix is ​​prepared is: .

Citation Information

Patent Citations

  • Fiber reinforced ceramic matrix composite bolt and preparation method thereof

    CN112552065A

  • Ceramic matrix composite stud and preparation method thereof

    CN112794718A

  • Preparation method of special thermal insulation material for graphite negative electrode material

    CN118196090A

  • Optimized preparation process of high-performance soldering flux

    CN118305493A

  • Intelligent preparation method of water-oxygen-resistant silicon carbide ceramic-based composite material

    CN118546003A

Cited By

  • Hard alloy bar vacuum sintering process capable of preventing deformation

    CN120885685A

  • High-strength ceramic matrix composite bolt and processing technology

    CN121449431A